Impact of urban agriculture on poverty at informal settlements in Soweto, Gauteng Province - Mankoe, Morore Mattheus (My University, 2013)
Urbanisation is one among the pressing issues facing human kind today and with it large number of rural poor immigrated to cities, failed by economic growth to get formal employments, large number of the poor are now found in informal settlements around cities where abject poverty, unemployment and extreme hunger is concentrated. Urban Agriculture is viewed as one of the strategies the urban poor employs to cushion themselves from the hardships of poor economic conditions. In contrast, there is a view that urban agriculture exploits labour, generates below poverty incomes and land fetches higher prices in cities, as such providing scarce public resources to this practice is not of economic importance. The purpose of this study was to explore the impact of urban agriculture on poverty, more precisely on the contribution of the practice towards job creation, cash incomes and food security. To determine if, urban agriculture can become a potential avenue for local economic development in the informal settlements of Soweto. Descriptive and quantitative assessments of the variables of urban agriculture in the study area were attempted to validate whether urban agriculture can emerge as a substantial mechanism to eradicate poverty and bring forth a potential area for local economic development in the study area. A questionnaire was used as an instrument for data collection. In the study, some of the facts revealed were that large proportion of the practitioners of urban agriculture are women and few went pass the matric. Moreover, large proportion of the urban farmers were doing so to supplement food at home and surplus sold, on average generating below poverty incomes and no job opportunities were recorded. The study concluded by providing recommendations on how city municipalities, development scientists and policy administrators can ensure that Urban Agriculture is supported in order to offer a potential avenue for local economic development. Some of the recommendations proposed, to cite a few, are that bottlenecks that limit development of Urban Agriculture must be removed, such as policy biasness, especially to livestock production in the cities, provision of infrastructure, tenure system and access to credits to improve productivity of the practice. Provision of advisory service must be conducted in indigenous language to improve adoptability and comprehension to facilitate technological transfer.
Thesis (M. Dev.) -- University of Limpopo, 2013
Keywords: Urban agriculture; Informal settlements; Urban agriculture; Land use, Urban -- South Africa -- Gauteng; Poverty -- South Africa -- Gauteng